2005
DOI: 10.1111/j.1365-2966.2005.09350.x
|View full text |Cite
|
Sign up to set email alerts
|

The AAO/UKST SuperCOSMOS Hα survey

Abstract: The UK Schmidt Telescope (UKST) of the Anglo-Australian Observatory completed a narrowband Hα plus [N II] 6548, 6584-Å survey of the Southern Galactic Plane and Magellanic Clouds in late 2003. The survey, which was the last UKST wide-field photographic survey and the only one undertaken in a narrow-band, is now an online digital data product of the Wide-Field Astronomy Unit of the Royal Observatory Edinburgh (ROE). The survey utilized a high specification, monolithic Hα interference bandpass filter of exceptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
276
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 311 publications
(282 citation statements)
references
References 63 publications
3
276
0
3
Order By: Relevance
“…16). Our predicted maximum Hα emission is above the diffuse emission sensitivity limit of the SuperCOSMOS H-alpha Survey (SHS Parker et al 2005) of 1.1−2.8 × 10 −17 erg s −1 cm −2 arcsec −2 , e.g. our model OSNR4040 has a maximum emission larger than 9 × 10 −16 erg s −1 cm −2 arcsec −2 (Fig.…”
Section: Emission Mapsmentioning
confidence: 99%
“…16). Our predicted maximum Hα emission is above the diffuse emission sensitivity limit of the SuperCOSMOS H-alpha Survey (SHS Parker et al 2005) of 1.1−2.8 × 10 −17 erg s −1 cm −2 arcsec −2 , e.g. our model OSNR4040 has a maximum emission larger than 9 × 10 −16 erg s −1 cm −2 arcsec −2 (Fig.…”
Section: Emission Mapsmentioning
confidence: 99%
“…About 2700 PNe have been detected so far in the Galaxy, including the objects listed by Acker et al (1994Acker et al ( , 1996 and the new PNe found in the Southern Hemisphere by the AAO-UKST Hα survey (Parker et al 2005;Miszalski et al 2008). However, the expected Galactic PN population is much larger, with estimates varying from 28000±5000 based on observations ) to 46000 ± 13000 PNe (of size <0.9 pc) derived from stellar population synthesis models (Moe & De Marco 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number (∼1200) of newly discovered PNe have been listed in the Macquarie/AAO/Strasbourg Hα PNe (MASH) PN catalogues (Miszalski et al 2008;Parker et al 2006) which are a direct product of the Anglo-Australian Observatory/UK Schmidt Telescope (AAO/UKST) Hα survey (Parker et al 2005). A significant fraction of MASH PNe represent the oldest stages of PN evolution, dominating the known population at the faint end of the PN luminosity function.…”
Section: Introductionmentioning
confidence: 99%